If it's not what You are looking for type in the equation solver your own equation and let us solve it.
42=3(x+4)
We move all terms to the left:
42-(3(x+4))=0
We calculate terms in parentheses: -(3(x+4)), so:We get rid of parentheses
3(x+4)
We multiply parentheses
3x+12
Back to the equation:
-(3x+12)
-3x-12+42=0
We add all the numbers together, and all the variables
-3x+30=0
We move all terms containing x to the left, all other terms to the right
-3x=-30
x=-30/-3
x=+10
| 3u+2u=130 | | 7y+y=21 | | P=-6-p | | 3f+1=10f= | | 5b=9=6+8b | | 7=27;x=3 | | 212=-w+82 | | 25-4cc=4 | | 28d=560 | | F(n)=−2n+1F(10)= | | 6(4+x)+5-3x+5x= | | 2x+4+x=15+6x-2 | | 4(8–2v)=112 | | -17c+12=4c+18c | | 5x-10=2x+5ç | | b+315=204 | | 8=q-15 | | 420n=680 | | 48-y=158 | | 17v=99 | | b-46/4=10 | | 4/3w=−12 | | 17v=98 | | 6x+15=23x | | -4(3b+4)=-27-11b | | b-205=723 | | 17v=97 | | 2x+6+4x-2=11x-6 | | 6=-y+182 | | 17v=96 | | 3v+2=8v= | | 3(u+1)=18u= |